EVALUATION OF MONITORING HYPERTENSION CASE BASED ON NINE SURVEILLANCE ATTRIBUTES IN JOMBANG DISTRICT HEALTH OFFICE IN 2018 - Dewi Lestari (Universitas Airlangga, 2021)
Hypertension is still a global problem, therefore, even affecting the citizens of Indonesia. Among 10 most common diseases in Jombang regency, hypertension was ranked second in 2017. One of the efforts in overcoming hypertension was by monitoring hypertension cases through Noncommunicable Diseases (NCD) surveillance system strengthening. However, the completeness of the MSS hypertension reports in Jombang region was low.The purpose of this study was to evaluate the monitoring of hypertension cases based on surveillance attributes in the Jombang District Health Office throughout 2018. This study was conducted using the qualitative evaluation method. The research subject was NCD surveillance, specifically in monitoring hypertension cases in the Jombang District Health Office. The determination of the informants used purposive sampling. The research informants consist of NCD officers in Jombang District Health Office, and NCD officers in 2 selected primary healthcare centers. The data collection technique used interview guidelines and document observation where data analysis was performed descriptively. The results show in the assessment of surveillance attributes of simplicity, acceptability, positive predictive value, data quality, and stability the results were low. While, flexibility, sensitivity, representativeness, and timeliness cannot be assessed. The conclusion was that the assessment of the surveillance attributes was quite good, but there are still obstacles in its implementation, namely incomplete reports, no attendance records, and so on. This study suggests to implement attendance records in each unit allowing the reported data to be used for planning in preventing hypertension.Keywords: evaluation, hypertention, surveillance attribute.